Millets (nutricereal)anditsvalue-addition:A review of the health benefits and future prospects (Journal of Food and Dietetics Research, 2022)
Today, feeding an exponentially growing population with increasing public health issues and global climate change is a significant challenge for many developing countries like India. To counter these issues, either we can increase production, spend a considerable amount on the public health sector, or look for other affordable and healthy alternatives such as millets. Millets can help tackle health challenges such as obesity, diabetes, and lifestyle problems for gluten-free properties, have a low glycemic index, and are high in dietary fiber and antioxidants. This paper reviews the prospects of millets to combat climate-change issues and achieve food and nutritional security. This review was done to highlight the nutritional values, health benefits, availability, and future prospectus of the millet and its value addition. The findings of the paper reveal that millets are ignored since the Green Revolution in India. There is a strong need to develop high value-added products from millets to streamline this crop with other staples to increase its consumption, such as a nutrition bar to meet modern world needs
Keywords: Millets; Nutricereal; Value-added products; Health benefits; Climate-change